Investigation of material properties and thermal stabilities of magnetron-sputter-deposited ZnO:Al/Ag/ZnO:Al transparent conductive coatings for thin-film solar cell applications - Van Eek, S (IOP Publishing, 2020)
10.7567/JJAP.56.08MA12